2018
DOI: 10.1021/acs.joc.8b00929
|View full text |Cite
|
Sign up to set email alerts
|

Method for Catalytic Enantioselective Alkylation of Aldehydes Using Grignard Reagents as Alkyl Sources

Abstract: Alkyltitanium reagents, generated in situ from Grignard reagents and ClTi(O Pr), can be employed without further manipulation in the enantioselective alkylation of aldehyde by the catalysis of a chiral titanium complex derived from DTBP-H-BINOL. The reaction is performed with good stoichiometry [1.5 equiv each of Grignard reagents and ClTi(O Pr)] at a low catalyst loading (2 mol %), affording a variety of chiral secondary alcohols in high enantioselectivity and yields and, hence, realizing an asymmetric versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…One drawback of these processes is the required removal of coproduced magnesium salts through centrifugation before adding the aldehyde partner to the reaction mixture. In 2018, Harada et al showed that it was possible to avoid this manipulation by generating the reactive alkyltitanium species from TiCl(Oi-Pr)3 instead of Ti(Oi-Pr)4 [12]. Indeed, R 2 MgX was treated with TiCl(Oi-Pr)3 (1.5 or 2 equiv) to give a mixture of R 2 Ti(Oi-Pr)3 and MgXCl.…”
Section: Alkylation Of Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…One drawback of these processes is the required removal of coproduced magnesium salts through centrifugation before adding the aldehyde partner to the reaction mixture. In 2018, Harada et al showed that it was possible to avoid this manipulation by generating the reactive alkyltitanium species from TiCl(Oi-Pr)3 instead of Ti(Oi-Pr)4 [12]. Indeed, R 2 MgX was treated with TiCl(Oi-Pr)3 (1.5 or 2 equiv) to give a mixture of R 2 Ti(Oi-Pr)3 and MgXCl.…”
Section: Alkylation Of Aldehydesmentioning
confidence: 99%
“…( Scheme 3. Alkylation of aldehydes with Grignard reagents in the presence of H8-BINOLderived ligand 5 [12].…”
mentioning
confidence: 99%